Community improvement practices through community schools in some selected areas of the Philippines and their implication for the army of knowledge of Iran - Najmabadi, Zahra 1932- ([Quezon City s.n.], 1969)
The purpose of this study is to make an investigation of the community improvement practices through community schools in selected areas in the Philippines. Knowledge of community development practices gained through this study may contribute to the success of the education corps in Iran
Thesis (M.Ed.)--University of the Philippines
Keywords: Community and school